Beyond taste: A sentiment analysis of informal language and cultural appreciation in Tripadvisor reviews of Balinese Ayam Betutu - Putu Pramania Adnyana; Kadek Wiweka; Amarjiva Lochan; Ni Luh Putu Trisdyani (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
This study investigates customer sentiment in online reviews of RM Ayam Betutu Pak Man, a renowned Balinese restaurant featured on TripAdvisor, one of the world’s leading platforms for culinary and tourism insights. In the digital era, online review technologies have revolutionized how restaurant businesses interact with customers and evaluate service quality. While previous research has examined sentiment analysis within the restaurant industry, limited attention has been given to establishments with deep cultural and culinary heritage. To address this gap, 77 TripAdvisor reviews from 2013 to 2020 were analyzed, encompassing six variables: name, title, rating, comment, date, and region. Data were processed using RStudio through text preprocessing, sentiment labelling, lexicon-based analysis, sentiment aggregation, and temporal trend examination. Results indicate that most reviewers are domestic tourists from major cities in Western Indonesia, with some international visitors from Dubai, Ipswich, Kuala Lumpur, Victoria, and Marcos. Overall, customer sentiment is predominantly positive, particularly regarding the taste and authenticity of ayam betutu, although fluctuations occur due to service quality issues and external factors such as the COVID-19 pandemic. Word cloud visualizations highlight the restaurant’s strong culinary reputation while pointing to service and cleanliness as areas for improvement. Strategically, the study suggests enhancing service quality, tailoring menus to diverse visitor preferences, and reinforcing digital and cultural branding. As a limitation, the analysis focused only on English and Indonesian reviews. Future studies are encouraged to include more languages, employ advanced analytical tools, and expand the dataset across various restaurant contexts.